Concomitant TP53 mutation in early-stage resected EGFR-mutated non-small cell lung cancer: a narrative approach in a genetically admixed Brazilian cohort - Machado-Rugolo, J. [UNESP] (2023)
TP53 mutations are frequent in non-small cell lung cancer (NSCLC) and have been associated with poor outcome. The prognostic and predictive relevance of EGFR/TP53 co-mutations in NSCLC is controversial. We analyzed lung tissue specimens from 70 patients with NSCLC using next-generation sequencing to determine EGFR and TP53 status and the association between these status with baseline patient and tumor characteristics, adjuvant treatments, relapse, and progression-free (PFS) and overall survival (OS) after surgical resection. We found the EGFR mutation in 32.9% of patients (20% classical mutations and 12.9% uncommon mutations). TP53 missense mutations occurred in 25.7% and TP53/EGFR co-mutations occurred in 43.5% of patients. Stage after surgical resection was significantly associated with OS (P=0.028). We identified an association between progression-free survival and poor outcome in patients with distant metastases (P=0.007). We found a marginally significant difference in OS between genders (P=0.057) and between mutant and wild type TP53 (P=0.079). In univariate analysis, distant metastases (P=0.027), pathological stage (IIIA-IIIB vs I-II; P=0.028), and TP53 status (borderline significance between wild type and mutant; P=0.079) influenced OS. In multivariable analysis, a significant model for high risk of death and poor OS (P=0.029) selected patients in stage IIIA-IIIB, with relapse and distant metastases, non-responsive to platin-based chemotherapy and erlotinib, with tumors harboring EGFR uncommon mutations, with TP53 mutant, and with EGFR/TP53 co-mutations. Our study suggested that TP53 mutation tends to confer poor survival and a potentially negative predictive effect associated with a non-response to platinum-based chemotherapy and erlotinib in early-stage resected EGFR-mutated NSCLC.